Cascaded Microwave Photonic Filters for Side Mode Suppression in a Tunable Optoelectronic Oscillator applied to THz Signal Generation & Transmission - G. K. M. Hasanuzzaman; Haymen Shams; Cyril C. Renaud; John Mitchell; Alwyn J. Seeds; Stavros Iezekiel (IEEE Photonics Journal)
We demonstrate experimentally an optoelectronic oscillator (OEO) in which high side-mode suppression is achieved by cascading a phase modulator-based single passband tunable microwave photonic (MWP) filter with an optoelectronic feedback loop-based infinite impulse response (IIR) MWP filter. The OEO provides an RF oscillation that can be tuned from 6.5 GHz to 17.8 GHz with a phase noise lower than -103 dBc/Hz. Experimental results show that inclusion of the IIR section leads to a 20 dB reduction of phase noise close to the carrier and an increase of 10 dB in side mode suppression, compared to the equivalent OEO without an IIR section. The OEO was used to drive an optical frequency comb generator to generate a THz signal at 242.6 GHz by optical heterodyning; inclusion of the IIR section increases suppression of the side modes neighboring the THz carrier. A radio over fiber link was then implemented at a 242.6 GHz carrier frequency, with transmission of a 24 Gbps signal over 40 km of fiber and a 30 cm wireless path at a bit error rate below the forward error correction limit. The proposed system may be applied to frequency reconfigurable THz links and radars.